Not observable complex numbers in the electrical engineer and the physicist - Никитинский, Валерий Афанасьевич; Пивоварова, Светлана Валериевна; Шабрацкий, Сергей Владимирович (Eastern-European Journal of Enterprise Technologies, 2012)
The equality zero amounts complex numbers is interpreted in quantum physicist, as absence anything in given place, unlike electric circuit with energy in reactive elements